The role of information quality, trust and anxiety on intention to buy food supplements at the time of COVID-19 outbreak - Najib, Mukhamad; Fahma, Farah; Suhartanto, Dwi; Sumardi, Retno Santi; Sabri, Mohamad Fazli (Emerald, 2022)
Purpose: The purpose of this study is to analyze the factors affecting consumer`s intention to buy food supplements during COVID-19 pandemic using the expanding theory of planned behavior model. The variables of perceived information quality, trust and anxiety are integrated in the model of this study. Design/methodology/approach: A total of 553 valid questionnaire responses were collected via an online survey in the epicenter of the pandemic in Indonesia, such as Jakarta and surrounding cities. To evaluate the causal links between latent variables, structural equation modeling was adopted using LISREL software. Before the research hypothesis had been tested, validity and reliability analysis was carried out to make sure the measurement can be used. Findings: The findings indicate that perceived information quality influences trust and anxiety, and then both of them influence attitude toward food supplements. Moreover, the intentions to buy food supplements are determined by the consumer`s attitude. Research limitations/implications: This study assumes all consumers have similar access to information because they are living in the greater Jakarta. Nevertheless, in fact, the access of information is not similar between age groups and locations. Future research may wish to differentiate evaluations of a full-information group from those of the limited-information groups. Originality/value: This study provides a model of consumers` buying intentions toward food supplement products in the time of a health crisis such as the COVID-19 pandemic as a novelty. The implications of this study provide meaningful direction for marketing decisions and policy interventions in developing food supplement industries.